Emergency laparoscopic myomectomy in a rare case of hemoperitoneum from uterine leiomyoma - D., Kavitha Yogini; G., Vishnu Priya; Dharshini, Sai; Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The most common benign tumour in reproductive age group –uterine leiomyoma can rarely present with bleeding into the peritoneal cavity leading to hemodynamic instability. A 36-year parous woman presented with acute abdomen and hypovolemic shock. Pregnancy test reported to be negative. Emergency laparoscopy was done and detected to have a surface bleeder and emergency laparoscopic myomectomy done.